From the Sea for the Sight: Marine Derived Products for Human Vision - Brillante, Simona; Galasso, Christian; Lauritano, Chiara; Carrella, Sabrina (Frontiers in Aging Neuroscience, 2022)
Visual impairment, at different degrees, produce a reduction of patient wellness which negatively impact in many aspects of working and social activities. Eye diseases can have common cellular damages or dysfunctions (e.g. inflammation, oxidative stress, neuronal degeneration), and can target several eye compartments, primarily cornea and retina. Marine organisms exhibit high chemical diversity due to the wide range of marine ecosystems where they live; thus, molecules of marine origin are gaining increasing attention for the development of new mutation-independent therapeutic strategies, to reduce the progression of retina pathologies having a multifactorial nature and characterized by high genetic heterogeneity. This review aims to describe marine natural products reported in the recent literature that showed promising therapeutic potential for the development of new drugs to be used to contrast the progression of eye pathologies. These natural compounds exhibited beneficial and protective properties on different in vitro cell systems and on in vivo models, through different mechanisms of action, including anti-inflammatory, antioxidant, antiangiogenic/vasoprotective or cytoprotective effects. We report compounds produced by several marine source (e.g. sponges, algae, shrimps) that can be administrated as food or with target-specific strategies. In addition, we describe and discuss the uses of opsin family proteins from marine organisms for the optimization of new optogenetic therapeutic strategies.